Physician as entrepreneur or platform worker? The challenge of introducing the legal presumption of an employment relationship within the self-employment model in healthcare - Chmielewska, Marta (Problem zakresu regulacji ustawowej nietypowych form zarobkowania na przykładzie zatrudnienia zewnętrznego i pracy platformowej, 2025)
The aim of this article is to address the issue of applying the presumption of an employment relationship, as expressed in Article 5 of the Platform Work Directive, to employment relationships established between digital labor platforms and representatives of independent professions, for whom conducting a sole proprietorship is a legally regulated form of practicing their profession. This issue is examined using the example of the medical profession in the context of the Polish legislator’s acceptance of widespread self-employment among this professional group in healthcare institutions. The study highlights the undefined scope of the employer’s direction in Polish legislation and the inability to establish a clear demarcation between employment contracts and civil law contracts. The adoption of the presumption may result in a differentiation of the legal status of doctors providing services through digital labor platforms, despite the existence of a lower degree of direction and control exercised by the employer, compared to typical relationships based on the selfemployment of doctors.